(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article discusses the incomparable role of books in human thought, spirituality and knowledge. Books are interpreted as an invaluable source that sharpens the human mind, encourages it to think, and guides it on the right path. The article also discusses the methods of introducing the younger generation to reading, the role of books in the era of modern information technologies, and their promotion. The cooperation of family, school, and society is noted as an important factor in the formation of a reading culture.